PELATIHAN KONSEP TRI NGA KI HAJAR DEWANTARA BAGI GURU DI SDNU PEMANAHAN - Syafriza, Azizatul Alif; Ferryka, Putri Zudhah (WIDHARMA - Jurnal Pengabdian Widya Dharma, 2025)
The purpose of writing this article is to provide training to teachers, especially at SDNU Sleman, regarding the concept of Tri Nga Ki Hajar Dewantara. The concept of "Ngerti, Ngrasa, Nglakoni" as a comprehensive learning, includes cognitive, affective, and psychomotor aspects. The learning process is not only about understanding and feeling, but also about implementing these values ​​in daily actions and behaviors. The application of the Tri Nga concept will create an active and enjoyable learning atmosphere. Active learning means that students are actively involved in class. Students have the ability and are accustomed to being involved and expressing their opinions. Enjoyable learning means that students feel happy during the learning process and can enjoy every learning process carried out so that the material learned can be more embedded in students' memories. It is hoped that after this socialization is carried out, teachers can create more enjoyable learning, so that learning becomes meaningful.